Screening for cognitive impairment in SLE using the Self-Administered Gerocognitive Exam. (July 2018) - Meara, A; Davidson, N; Steigelman, H; Zhao, S; Brock, G; Jarjour, W N; Rovin, B H; Madhoun, H; Parikh, S; Hebert, L; Ayoub, I; Ardoin, S P
Objective: Systemic lupus erythematosus (SLE) is a multisystem autoimmune disease that can affect the central nervous system in multiple ways, including causing cognitive dysfunction. Cognitive dysfunction is a common complaint of SLE patients yet diagnosis is challenging, time consuming, and costly. This study evaluated the Self-Administered Gerocognitive Exam (SAGE) as a screening test for cognitive impairment in a cohort of SLE patients. Methods: A total of 118 SLE patients completed the SAGE. Providers completed the Systemic Lupus Erythematosus Disease Activity Index (SLEDAI) and the Systemic Lupus International Collaborative Clinics Damage Index (SLICC-DI). SAGE scores were grouped into normal (>16) and abnormal (≤16) categories. Univariate and multivariate analyses were performed. Results: Of the 118 participants, 21(18%) scored ≤16 on the SAGE instrument. In univariate analysis, race, ethnicity, household income, and SLICC-DI scores were associated with the SAGE ( p  < 0.05). In multivariable analysis, abnormal SAGE score was independently associated with higher SLICC-DI score (odds ratio (OR) = 1.44, 95% confidence intervals 1.04–1.99, p  = 0.03)), Hispanic ethnicity (OR = 43.4, 95% CI 3.1–601, p  = 0.005), and lower household income (OR = 11.9 for ≤$15, 000 vs >$50, 000, 95% CI 2.45–57, p  = 0.002). Conclusions: In SLE patients, this study demonstrates an independent relationship between neurocognitive impairment (as measured by the SAGE) and higher lupus-related damage, as measured by the SLICC-DI, and lower household income. Abnormal SAGE scores were also associated with Hispanic ethnicity. A language barrier could explain this because the SAGE instrument was conducted in English only. The SAGE was feasible to measure in the clinic setting.